A Commercial Benchmark: Light‐Soaking Free, Fully Scalable, Large‐Area Organic Solar Cells for Low‐Light Applications. Issue 9 (18th January 2021) - Luke, Joel; Corrêa, Luiza; Rodrigues, Jair; Martins, Juliana; Daboczi, Matyas; Bagnis, Diego; Kim, Ji‐Seon
Abstract: Low‐light applications provide an exciting market opportunity for organic solar cells (OSCs). However, so far, studies have only considered OSCs of limited commercial viability. Herein, the applicability of a fully‐scalable, flexible, inverted non‐fullerene acceptor (NFA) containing OSC is demonstrated by showing its superior performance to silicon under low‐light, achieving 40 µW cm −2 maximum power output at 1300 lx illumination. The effect of parasitic resistance and dark current on low‐light performance are identified. Furthermore, an atmosphere sensitive light‐soaking (LS) effect, critical for low‐light performance and resulting in undesirable S‐shaped current‐voltage characteristics, is analyzed. By employing different interlayers and photoactive layers (PALs) the origin of this LS effect is identified as poor electron extraction at the electron transport layer (ETL)/PAL interface when the common ETL ZnO is used. Two strategies are implemented to overcome the LS effect: replacement of ZnO with SnO2 nanoparticles to reduce ETL sub‐gap electron trap states or tuning the NFA energy levels to optimize interfacial energetics. Finally, the commercial viability of these LS‐free devices is demonstrated by fabricating fully printed large‐area modules (21.6 cm 2 ) achieving a maximum power output of 17.2 µW cm −2, providing the most relevant example of the currently obtainable performance in commercial low‐light OSCs. Abstract : Organic solar cells (OSCs) outperform other technologies at low‐light intensities providing an exciting opportunity for commercialization. Previous OSC low‐light studies utilize non‐scalable materials or methods unsuitable for commercialization. Scalable materials are used to highlight the current performance of commercially relevant low‐light OSCs. The effect of parasitic resistance and a light‐soaking effect that is critical for low‐light performance are also investigated.